Pulmonary rehabilitation at a time of social distancing: prime time for tele-rehabilitation? - Linzy Houchen‐Wolloff; Michael Steiner (2020)
The global COVID-19 pandemic and the concomitant social distancing measures taken in many countries to suppress transmission of the virus has had an immediate and profound effect on the provision of pulmonary rehabilitation (PR) services. Conventional PR programmes organised around groups of people attending a rehabilitation centre have been suspended in most affected countries to ensure vulnerable people are effectively shielded from the virus. However, the need for PR has not gone away and consideration is under way about how best to provide effective therapy in the context of the current crisis.1 2 The issue of enhancing access to effective PR is not a new one. The overwhelming evidence for the effectiveness of the intervention (reducing disability, improving quality of life3 and potentially offering a survival advantage for those who complete the programme4) has been tempered by well-documented problems across many healthcare systems in ensuring PR is accessible for all who need it.5 It is this problem that has taken centre stage in the field in recent years, and the need for innovation in the delivery of PR is a clear and urgent challenge in the context of the current pandemic.